New Contributions on Flora and Vegetation of northeastern Portugal ultramafic outcrops - Aguiar, Carlos; Monteiro-Henriques, Tiago; Sánchez-Mata, Daniel (Lazaroa, 2013)
In this work we present some syntaxonomic novelties on the vegetation of the referred ultramafic outcrops focused onthree new associations: Jonopsidio abulensis-Sedetum maireani, Armerio daveaui-Agrostietum castellanae and Seseli peixotoani-Avenuletum lusitanicae; in addition, a new nomenclatural combination of an endemic taxon from the Morais massif(Armeria langei subsp. marizii) is proposed. We also clarify the phytocoenotic structure of the Portuguese vegetation seriesthrough a simple diagrammatic representation, which is then applied to one unique climatophilous vegetation series presentin the ultramafic rocks of northeastern Portugal: Genisto hystricis-Querco rotundifoliae Sigmetum.